If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = (cx + 3)(c + -2) Reorder the terms: x = (3 + cx)(c + -2) Reorder the terms: x = (3 + cx)(-2 + c) Multiply (3 + cx) * (-2 + c) x = (3(-2 + c) + cx(-2 + c)) x = ((-2 * 3 + c * 3) + cx(-2 + c)) x = ((-6 + 3c) + cx(-2 + c)) x = (-6 + 3c + (-2 * cx + c * cx)) x = (-6 + 3c + (-2cx + c2x)) x = (-6 + 3c + -2cx + c2x) Solving x = -6 + 3c + -2cx + c2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2cx' to each side of the equation. 2cx + x = -6 + 3c + -2cx + 2cx + c2x Combine like terms: -2cx + 2cx = 0 2cx + x = -6 + 3c + 0 + c2x 2cx + x = -6 + 3c + c2x Add '-1c2x' to each side of the equation. 2cx + -1c2x + x = -6 + 3c + c2x + -1c2x Combine like terms: c2x + -1c2x = 0 2cx + -1c2x + x = -6 + 3c + 0 2cx + -1c2x + x = -6 + 3c Reorder the terms: 6 + -3c + 2cx + -1c2x + x = -6 + 3c + 6 + -3c Reorder the terms: 6 + -3c + 2cx + -1c2x + x = -6 + 6 + 3c + -3c Combine like terms: -6 + 6 = 0 6 + -3c + 2cx + -1c2x + x = 0 + 3c + -3c 6 + -3c + 2cx + -1c2x + x = 3c + -3c Combine like terms: 3c + -3c = 0 6 + -3c + 2cx + -1c2x + x = 0 The solution to this equation could not be determined.
| 9x-12y=-21 | | 2ln*2x^2=6 | | 25-(3x-2)=25 | | 3*-3-5y=17 | | 4x^2-100=36 | | 10/8x-36=0 | | 8=y/4-8 | | 5x(x)=16(125) | | 2p^2+5p-3p^4+2p+p^5-2+8= | | y+5*4=9 | | 51-6x=3x+22 | | y+5*0=9 | | 2x-1=4.5 | | x+20=180 | | y+5*-2=9 | | 27(3)=x(x) | | (7/(4x-1))=(2/(x+5)) | | 6-7x=66-35x | | 3x+25+2x+15+x+20=180 | | 9(16)=x(x) | | x+20+2x+15+3x+25=180 | | 3(2r+7)+2(4r+1)=37 | | 7/(4x-1) | | y+4*-1=9 | | 9(x)=16(x) | | y+4*4=9 | | y+4*0=9 | | y+4*8=9 | | 3x^2-8=67 | | 5x+12x+19x=180 | | 3x-5=4x+7 | | y+4-1=9 |